Habitual salt preference worsens blood pressure in hospitalized hypertensive patients with omicron infection under epidemic-related stress - Chenyi Wang; Wanhong Tan; Xiaoxiao Liu; Miao He; Shi Zeng; Maojie Sun; Lijuan Yan; Min Li; Kun Zhan; Kaifa Wang; Qiang Li (BMC, 2024)
Abstract Background We investigated the synergistic effect of stress and habitual salt preference (SP) on blood pressure (BP) in the hospitalized Omicron-infected patients. Methods From 15,185 hospitalized Omicron-infected patients who reported having high BP or hypertension, we recruited 662 patients. All patients completed an electronic questionnaire on diet and stress, and were required to complete morning BP monitoring at least three times. Results The hypertensive group (n = 309) had higher habitual SP (P = 0.015) and COVID-19 related stress (P < 0.001), and had longer hospital stays (7.4 ± 1.5 days vs. 7.2 ± 0.5 days, P = 0.019) compared with controls (n = 353). After adjusting for a wide range of covariates including Omicron epidemic-related stress, habitual SP was found to increase both systolic (4.9 [95% confidence interval (CI), 2.3-7.4] mmHg, P < 0.001) and diastolic (2.1 [95%CI, 0.6-3.6] mmHg, P = 0.006) BP in hypertensive patients, and increase diastolic BP (2.0 [95%CI, 0.2-3.7] mmHg, P = 0.026) in the control group. 31 (8.8%) patients without a history of hypertension were discovered to have elevated BP during hospitalization, and stress was shown to be different in those patients (P < 0.001). In contrast, habitual SP was more common in hypertensive patients with uncontrolled BP, compared with patients with controlled BP (P = 0.002). Conclusions Habitual SP and psychosocial stress were associated with higher BP in Omicron-infected patients both with and without hypertension. Nonpharmaceutical intervention including dietary guidance and psychiatric therapy are crucial for BP control during the long COVID-19 period.